Minigrid integration planning (MGIP) for loss reduction and voltage profile improvement beyond energy access in developing countries. (November 2022) - Chikumbanje, Madalitso; Frame, Damien; Galloway, Stuart
Abstract: To improve access to electricity and achieve Sustainable Development Goal 7 (SDG7), a mixture of grid extension and off-grid systems, like minigrids, are under deployment in many developing countries, including sub-Saharan Africa (SSA). Beyond meeting energy access goals, the main grid will continue expanding and eventually converge and integrate with minigrids. Such integration has the potential to address network losses and low quality of supply in developing countries, similar to how the optimal placement and sizing of distributed energy resources (DERs) has impacted distribution networks in the global north. However, unlike in the DER integration, there is no suitable planning methodology for maximizing the benefits of grid integration of formerly autonomous minigrids in developing countries. This paper proposes a minigrid integration planning (MGIP) methodology that ensures loss reduction and voltage improvement in post-energy access networks in developing countries. The planning problem is formulated as a mixed-integer non-linear problem (MINLP) and is solved using a Genetic Algorithm (GA). The paper demonstrates MGIP's ability to ensure loss reduction and voltage profile improvement by identifying optimal points of grid infeed into formerly autonomous minigrids. It also shows MGIP's flexibility to be applicable in a basic case of integrating a single minigrid and an advanced case of integrating a cluster of minigrids. The results show that using the MGIP approach can significantly reduce losses (by up to 65% as observed in some scenarios of the reported case studies) and improve voltage profile through the grid integration of formerly autonomous minigrids in the post-SDG7 electrical networks in developing countries. Highlights: Beyond universal electricity access, the performance of electricity supply systems needs to improve in developing countries. A power system analysis and optimization-based methodology, MGIP, is proposed for planning the grid integration of minigrids. MGIP identifies optimal points of grid infeed into autonomous minigrids to improve the performance of the integrated network. Loss reduction potential of up to 65%, and significant voltage profile improvement are realised in the reported MGIP usage.